Development of an Efficient Load Frequency Controller for Pico Hydropower Generation System in Sewage Treatment Plant - Jalil A.F.A.; Pasupuleti J.; Khan M.R.B. (Institute of Electrical and Electronics Engineers Inc., 2023)
Asynchronous generators; Climate change; Cost effectiveness; Effluents; Electric control equipment; Electric frequency control; Electric loads; Flow rate; Fossil fuels; Hydraulic machinery; Hydraulic motors; Hydraulics; Hydroelectric generators; Hydroelectric power; Hydroelectric power plants; MATLAB; Power quality; Press load control; Quality control; Rivers; Three term control systems; Water quality; Electronic load controller; Final effluents; Fuzzy PID controller; Generation systems; Hydro-power generation; Hydropower; Hydropower plants; Incoming flows; Load frequency controllers; PID controllers; Controllers